ESTRUS RESPONSE HOLSTEIN FRIESIAN COW PERANAKAN WHO INJECTED PROSTAGLANDIN IN INTRAMUSCULAR AND INTRAUTERINE - Nuryanto, Lilik Bawa; Handarini, Ristika; Setiawan, Yanyan (Jurnal Peternakan Nusantara, 2017)
This study was aimed to compare the different responses of cattle estrus and pregnancy rate FH (Friesian Holsein) were injected with the prostaglandin hormone by intramuscular and intra-uterine. This study was used 20 cows FH on condition of normal reproductive function, not in a state of pregnant (confirmed by rectal palpation), visually not fat and not skinny, not reproductive disease, normal estrous cycles. Cows were divided into two treatment, P1: estrus synchronization by intra muscular (IM), P2: estrus synchronization by  intrauterine (IU). Data were analyzed by T test, to compare the differences between the two treatments with SPSS device. The results showed that the synchronization of pregnancy by using intrauterine more efisien. The conclusion of this research PGF2α hormone injections by intrauterinehas atendency response   higher than by intra muscular injection method.               Keyword : Non Return Rate, Service Per Conception, Conception Rate.